2003
DOI: 10.1002/jssc.200301470
|View full text |Cite
|
Sign up to set email alerts
|

Matching average masses of pitch fractions of narrow polydispersity, derived from matrix‐assisted laser desorption ionisation time‐of‐flight mass spectrometry, with the polystyrene calibration of SEC

Abstract: Matching average masses of pitch fractions of narrow polydispersity, derived from matrix-assisted laser desorption ionisation time-of-flight mass spectrometry, with the polystyrene calibration of SEC A coal tar pitch has been fractionated by preparative and analytical size exclusion chromatography (SEC) to provide narrow time-elution fractions, expected to have relatively low molecular dispersities. The fractions were characterised by analytical SEC, by UV-fluorescence spectroscopy, and by laser-desorption MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 21 publications
4
57
0
Order By: Relevance
“…Using APPI ionization, the fragmentation is largely reduced and, therefore, the masses detected should be more representative of the true MW of the sample. The mass range found, between m=z 250-1100 with a maximum at m=z 500-600, is in very good agreement with previous works (Hortal et al, 2007;Merdrignac, 2007;Rizzi et al, 2006), whereas the eventual presence of higher masses (>100,000 u), as found by other authors (Islas et al, 2003;Karaka et al, 2004), cannot be investigated because the mass limit of the ion trap mass spectrometer is about 3000-4000 u for single-ionized analytes.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Using APPI ionization, the fragmentation is largely reduced and, therefore, the masses detected should be more representative of the true MW of the sample. The mass range found, between m=z 250-1100 with a maximum at m=z 500-600, is in very good agreement with previous works (Hortal et al, 2007;Merdrignac, 2007;Rizzi et al, 2006), whereas the eventual presence of higher masses (>100,000 u), as found by other authors (Islas et al, 2003;Karaka et al, 2004), cannot be investigated because the mass limit of the ion trap mass spectrometer is about 3000-4000 u for single-ionized analytes.…”
supporting
confidence: 91%
“…The true MW range of asphaltenes is still object of high-pitched debate (Herod et al, 2008;Mullins et al, 2008). Many authors proposed a relatively low MW range of m=z 500-1000 (Badre et al, 2005;Mullins, 1999, 2000), whereas others (Islas et al, 2003;Karaka et al, 2004) found basically bimodal distributions with two mass ranges: the former between m=z 100 and 3,000 and the latter corresponding to masses higher than m=z 100,000. Even though the high MW range could be overestimated due to the three-dimensional conformation (or large hydrodynamic volumes) adopted by the larger asphaltene molecules, these authors claimed the presence of big molecule of at least 10,000 u (Herod et al, 2008).…”
Section: Mass Spectrometry Of Large Aromatic Molecules 643mentioning
confidence: 99%
“…Calibration of SEC using small molecules (up to 1100 u with different functional groups) and various polymer standards was in agreement (within a factor of two) with the masses of these known compounds and fractions of pitch of low polydispersity for which the mass at peak ion abundance (Mp) was measured by MALDI‐MS 1, 7–9. The calibration of SEC apparently applied only to that material eluting within the porosity range of the SEC column, but not to the material excluded from the porosity.…”
mentioning
confidence: 53%
“…The application of the SEC technique to MW determination relies on the use of standard materials that have the same structures as the components of the samples. The polystyrene calibration of SEC has been shown to predict the molecular masses of fractions of coal tar pitch, separated by preparative SEC, for which the average masses were determined by matrix-assisted laser desorption/ionization (MALDI)-MS and laser desorption (LD)-MS. 18 In addition, other standard aromatic species of known molecular mass, such as ovalene, dicoronylene and polyacenaphthylene, eluted as predicted by the polystyrene standard calibration curve, demonstrating that the attribution of MW of carbon particulates on the basis of polystyrene standards is likely to be reliable. 16 An alternative tool for the determination of MW is the MALDI-time-of-flight (TOF)-MS technique that can give, in principle, a direct measure of MW without the necessity for a standard compound.…”
mentioning
confidence: 92%